1999
DOI: 10.1103/physrevb.60.10504
|View full text |Cite
|
Sign up to set email alerts
|

Role of structural disorder in artificially layered high-temperature superconductors

Abstract: The electrical transport properties of (BaCuO 2 ) 2 /(CaCuO 2 ) 2 superconducting artificial structures, grown by pulsed laser deposition stacking in sequence nonsuperconducting individual BaCuO 2 and CaCuO 2 layers, have been studied. Such artificially layered materials have T c values up to 80 K and show a number of unusual properties such as the relatively high normal state resistivity with a nonlinear dependence on temperature, the enhanced thermodynamic fluctuations, the relatively low value of the critic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
20
0

Year Published

2000
2000
2025
2025

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 27 publications
1
20
0
Order By: Relevance
“…Thinner CR blocks (M 3) resulted in a decrease of T c possibly because of the occurrence of interface effects at the substrate/film and film/cap-layer interfaces. Furthermore, structures with N 1 were found to have a lower T c possibly because of the increased role of structural disorder in such thin IL blocks [26]. Therefore we decided to carry out J c measurements mostly on 5=2=5 structures and 2 2 superlattices.…”
mentioning
confidence: 99%
“…Thinner CR blocks (M 3) resulted in a decrease of T c possibly because of the occurrence of interface effects at the substrate/film and film/cap-layer interfaces. Furthermore, structures with N 1 were found to have a lower T c possibly because of the increased role of structural disorder in such thin IL blocks [26]. Therefore we decided to carry out J c measurements mostly on 5=2=5 structures and 2 2 superlattices.…”
mentioning
confidence: 99%
“…4 These superlattices, grown under appropriate temperature and oxygen pressure conditions, can have a superconducting transition temperature T c as high as 80 K. 12 All their superconducting properties are drastically affected by the large degree of structural disorder present. 13 Recently it has been shown by EXAFS and x-ray diffraction measurements in (Ba 2 Cu 2 O 4ϩx )/(CaCuO 2 ) n superlattices 14,15 that the crystallographic structure of the Ba block consists of a sequence of four atomic planes, namely CuO 2 /BaO/Cu 1Ϫ␦ O x /BaO with c 1 ϭ8.9 Å. The Ca block consists of a sequence of CuO 2 and Ca planes and has a true infinite layer ͑IL͒ structure with c 2 ϭ3.2 Å.…”
Section: Introductionmentioning
confidence: 97%
“…It decreases both for n larger than 3 and smaller than 2. Such an effect was explained on the basis of the structural disorder (especially effective for small n) and of the variation of the effective carriers concentration with n. Furthermore it was demonstrated that some peculiar features of the temperature dependence of the resistivity (its relatively high residual value, its pronounced rounding above T c and its saturation above room temperature) can be well explained by taking into account the role of the interfacial structural disorder that arises at the blocks interfaces [4]. Following this considerations, we believe that the role of the structural disorder is strongly reduced for the superlattices with thick IL blocks, negligible for the thickest ones.…”
mentioning
confidence: 96%
“…In our previous work on the CBCCO − 2 × n system, we investigated both the dependence of the critical temperature on n (for n ranging from 1 to 6) and the influence of the interfacial structural disorder, typical for these artificial structures, on the electrical transport properties [4,5]. It was found that the critical temperature reaches the maximum value of about 80 K for n between 2 and 3.…”
mentioning
confidence: 99%
See 1 more Smart Citation